2022
DOI: 10.1111/brv.12839
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the ecological and evolutionary function of stopover in migrating birds

Abstract: Global movement patterns of migratory birds illustrate their fascinating physical and physiological abilities to cross continents and oceans. During their voyages, most birds land multiple times to make so-called 'stopovers'. Our current knowledge on the functions of stopover is mainly based on the proximate study of departure decisions. However, such studies are insufficient to gauge fully the ecological and evolutionary functions of stopover. If we study how a focal trait, e.g. changes in energy stores, affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 329 publications
2
94
0
Order By: Relevance
“…accumulating energy stores. By that, we ensured that all birds carried sufficient and comparable energy stores important for high motivation to resume migration, as many studies have shown a significant positive correlation between energy stores and departure probability ( Schmaljohann et al, 2022 ; Schmaljohann and Eikenaar, 2017 ; Klinner et al, 2020 ; Eikenaar et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…accumulating energy stores. By that, we ensured that all birds carried sufficient and comparable energy stores important for high motivation to resume migration, as many studies have shown a significant positive correlation between energy stores and departure probability ( Schmaljohann et al, 2022 ; Schmaljohann and Eikenaar, 2017 ; Klinner et al, 2020 ; Eikenaar et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…During stopover, migratory birds accumulate fuel (mostly lipids) to enable the following flight and to safeguard against starvation (Alerstam and Lindström, 1990;McWilliams et al, 2004;Kobylkov et al, 2014;Guglielmo, 2018). Yet, the stopover period may have several additional functions that may affect bird fitness, including physiological recovery from enduring flight and avoidance of inclement meteorological conditions during flight (Schmaljohann et al, 2022). How long to stay in a stopover site and how much fuel to deposit before departing from the site are two related questions with fitness consequences.…”
Section: Introductionmentioning
confidence: 99%
“…We observed stopover behavior of tagged bats before departing from Helgoland (the female) and when arriving at the mainland: After reaching the mainland, the male bat spent several days without moving longer distances before continuing its westward journey. Yet, in case of these stopovers, the underlying motivation remains unclear and might be manifold (Schmaljohann et al, 2022). Refueling fat stores, resting or recovering before continuing the journey might be possibilities.…”
Section: Discussionmentioning
confidence: 99%